Li‐Intercalation Oxides: Atomic‐Scale Observation of LiFePO4 and LiCoO2 Dissolution Behavior in Aqueous Solutions (Adv. Funct. Mater. 45/2018). (5th November 2018) - Byeon, Pilgyu; Bae, Hyung Bin; Chung, Hee‐Suk; Lee, Sang‐Gil; Kim, Jin‐Gyu; Lee, Hyeon Jeong; Choi, Jang Wook; Chung, Sung‐Yoon
Abstract : Dissolution behavior of cathode materials, LiCoO2 and LiFePO4, in aqueous electrolytes is investigated at an atomic level. In article number1804564 Sung‐Yoon Chung and co‐workers use scanning transmission electron microscopy, in particular, to characterize an unusual cation occupancy in the tetrahedral interstices in LiCoO2 during Co dissolution. This atomic‐scale observation provides a valuable contribution toward suppressing surface instability and thereby improving long‐term stability of cathode materials in aqueous Li‐ion batteries.